Imagine the teacher you want to be: a descriptive case study of beliefs about teaching - Sarmiento Lozano, Yessica Alejandra; Arroyo Cervantes, Luz Mery; López Fonseca, Yury Natalia (Corporación Universitaria Minuto de Dios, 2018)
The main objective of this case study is to analyze the way first semester students at Uniminuto University imagine themselves as English teachers. The researches were focused on analyzing their beliefs about teaching and how these are a relevant influence in their learning process as pre service teachers. Since the authors interpreted student’s feelings, perceptions, opinions, and beliefs about teaching, this research has a qualitative paradigm. In order to collect the information needed to answer the research question, this study employed three different instruments to collect data which are: questionnaires, drawings (comics) and interviews. These instruments, provided information to carry out the analysis and select a series of categories of analysis in different dimensions that compound the teaching profession. After the analysis, it was possible to determine that first semester students possess a series of beliefs about language teaching, these are not specific and clear because they have not been implicit in real situations as teachers.
Keywords: Beliefs; Experiences; Education; Teaching; Students; Administración de Personal Docente; Educación; Administración Escolar; Formación Profesional de Maestros